2007
DOI: 10.1016/j.jacc.2007.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Active Coxsackieviral B Infection Is Associated With Disruption of Dystrophin in Endomyocardial Tissue of Patients Who Died Suddenly of Acute Myocardial Infarction

Abstract: Our findings demonstrate a significantly higher proportion of active coxsackievirus B cardiovascular infections in patients who suddenly died of MI compared with matched control subjects, suggesting that these EVs may significantly contribute to the pathogenesis of acute MI by a focal disruption of the dystrophin-glycoprotein complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 31 publications
3
38
0
1
Order By: Relevance
“…A surveillance study of SCD from Ireland concluded that the majority of cases occurred in home and that successful resuscitation of SCD was especially associated with ventricular fibrillation as presenting rhythm (95). A recent study reported evidence for the occurrence of active Coxsackie B viral infections in people who died of MI compared to controls, and the authors suggested that an underlying mechanism might be disruption of dystrophin in endomyocardial tissue (96).…”
Section: Sudden Cardiac Death (Scd)mentioning
confidence: 99%
“…A surveillance study of SCD from Ireland concluded that the majority of cases occurred in home and that successful resuscitation of SCD was especially associated with ventricular fibrillation as presenting rhythm (95). A recent study reported evidence for the occurrence of active Coxsackie B viral infections in people who died of MI compared to controls, and the authors suggested that an underlying mechanism might be disruption of dystrophin in endomyocardial tissue (96).…”
Section: Sudden Cardiac Death (Scd)mentioning
confidence: 99%
“…This sensitivity of detection, is crucial because TD mutants replicate slowly and to low titers (7,10,11). This will be important for future work and may explain past inability to detect RNA despite viral capsid protein VP1 detection (1).…”
mentioning
confidence: 99%
“…Such hinge regions have been correlated with efficacy of the engineered minidystrophin construct in mouse models of DMD [9]. As well, specific protease sensitivity sites in dystrophin have been linked to various pathologies involving viral infection and heart attack [24,25].…”
Section: Discussionmentioning
confidence: 99%